A low temperature gas sensor based on Au-loaded MoS2 hierarchical nanostructures for detecting ammonia. Issue 7 (15th May 2016) - Yan, Huihui; Song, Peng; Zhang, Su; Zhang, Jia; Yang, Zhongxi; Wang, Qi
Abstract: Two-dimensional molybdenum disulfide (MoS2 ) is one kind of the promising candidate for gas sensing materials at low temperature. Meanwhile, surface modification with noble metals is considered as an effective strategy to enhance gas sensing performance. In this work, a novel gas sensing material was prepared by decorating Au nanoparticles on MoS2 hierarchical nanostructures. The morphology and microstructure were characterized by X-ray diffraction (XRD), X-ray photoelectron spectra (XPS), field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). The results clearly reveal that Au nanoparticles with sizes of 10–20 nm were deposited on the surface of MoS2 nanosheets, remaining isolated from each other and the dispersion is very uniform. Furthermore, the MoS2 hierarchical nanostructures are further employed as a support to load Au nanoparticles to construct nanocomposites for chemical gas sensors. Experimental results indicated that the Au nanoparticles-functionalized MoS2 hierarchical nanostructures, combining the high surface and catalytic activity of small Au nanoparticles demonstrated gas-sensing performance to NH3 at low temperature.